Effects of Extra Virgin Olive Oil and Apples Enriched-Dark Chocolate on Endothelial Progenitor Cells in Patients with Cardiovascular Risk Factors: A Randomized Cross-Over Trial - Francesca Felice; Alessandra Francini; Valentina Domenici; Mario Cifelli; Ester Belardinelli; Luca Sebastiani; Claudio Cantini; Rossella Di Stefano (MDPI AG, 2019)
Background: Endothelial dysfunction has been associated to cardiovascular outcomes in patients with cardiovascular risk factors. Circulating endothelial progenitor cells (EPCs) play an important physiological role for their reparative potential of vascular integrity, but are numerically reduced and functionally impaired in patients with cardiovascular risks. This study assesses the effects of Extra Virgin Olive Oil (EVOO) and apple-enriched dark chocolate intake on the blood levels of EPCs. Methods: Thirty volunteers with cardiovascular risk factors, enrolled in a randomised, crossover, four-weeks trial, received a solid dark chocolate bar (40 g/day) containing 10% EVOO or 2.5% dry apples. Urine samples were analyzed for endogenous metabolites. Circulating EPCs levels, clinical data and anthropometric examinations were collected. Results: 26 volunteers (M/F:14/12, 51 ± 9 years of age) completed the study. Comparison of pre-post intervention revealed a significant increase in EPCs levels associated with EVOO-dark chocolate consumption. Most biochemical parameters were not significantly modified by both chocolates. Conclusions: This study shows that a daily consumption of a non fattening dose of dark chocolate enriched with EVOO improves blood levels of EPCs, a well known surrogate biologic marker for endothelial function.